2016
DOI: 10.1002/dev.21399
|View full text |Cite
|
Sign up to set email alerts
|

Stress reactivity speeds basic encoding processes in infants

Abstract: Acute stress attenuates frontal lobe functioning and increases distractibility while enhancing subcortical processes in both human and nonhuman animals (Arnsten, 1998, Arnsten et al., 1998, Skosnik, 1999. To date however these relations have not been examined for their potential effects in developing populations. Here, we examined the relationship between stress reactivity (infants' heart rate response to watching videos of another child crying) and infant performance on measures of looking duration and visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…This suggests that the increase in arousal may have enhanced the infants’ attention to novel stimuli. Previous studies have also suggested that infants who react with higher arousal to stress and sensory input may also be more attentive to faces, as well as to other salient stimuli (de Barbaro, Clackson, & Wass, ; Jones, Dawson, & Webb, ). This study sought to extend knowledge about this relation by experimentally manipulating short‐term arousal.…”
Section: Phasic Alerting and Arousalmentioning
confidence: 99%
“…This suggests that the increase in arousal may have enhanced the infants’ attention to novel stimuli. Previous studies have also suggested that infants who react with higher arousal to stress and sensory input may also be more attentive to faces, as well as to other salient stimuli (de Barbaro, Clackson, & Wass, ; Jones, Dawson, & Webb, ). This study sought to extend knowledge about this relation by experimentally manipulating short‐term arousal.…”
Section: Phasic Alerting and Arousalmentioning
confidence: 99%
“…These changes are thought to be adaptive insofar as downregulated frontal activity and upregulated subcortical activity during periods of acute stress allows animals to more rapidly ascertain potential risks and respond to uncertainties in the environment with learned or pre-potent actions (Aston- Jones & Cohen, 2005;Dayan & Yu, 2003). Consistent with this, previous research examining a cohort of small-town dwelling infants has shown that infants with elevated physiological stress show both reduced visual sustained attention, and superior recognition memory for briefly presented images (de Barbaro, Clackson, & Wass, 2016b).…”
Section: Introductionmentioning
confidence: 82%
“…For example, previous research suggesting that increased physiological stress associates with both poorer sustained attention and superior recognition memory in a cohort of small-town-dwelling 12-month-old infants (de Barbaro et al, 2016b). Infant learning and attention is thought to be relatively more subcortically mediated than equivalent cognitive functions in adults (Colombo, 2001;de Barbaro et al, 2016b;Johnson, 1990), and previous research has suggested that recognition memory tasks may be subcortically mediated (Alvarez, Zola-Morgan, & Squire, 1995) -in contrast to sustained attention, which even in infants, is considered cortically mediated (Xie, Mallin, & Richards, 2018). The increased theta power we observed in HD infants was evenly distributed across the scalp (Fig 3), consistent with previous research (Jones et al, 2015;Orekhova et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iii) Previous research has suggested that, whereas voluntary, 'top-down' attention control is highest during mid-level arousal, some aspects of memory encoding should be highest during hyper-arousal (Arnsten, 2009;de Barbaro et al, 2016;Wass, de Barbaro, et al, under review). Future research should explore in more detail the strengths, as well as the weaknesses, of the hyper-aroused behavioral phenotype.…”
Section: Implications For Understanding Differential Susceptibility Tmentioning
confidence: 99%